Writing Abilities in Compulsive Prisoners - Muñoz-López, Lucas; López-Torrecillas, Francisca; Martín, Ignacio; Sánchez-Barrera, María Blasa; López-Torrecillas, María del Carmen; Serrano, Francisca (Frontiers in Psychology, 2021)
Research has found links between academic failure and criminal offending and suggest that many incarcerated young people have experienced significant behavioural and learning problems in school, which could result in criminal outcomes and poor academic performance. The objective of this study was to analyse writing disorders in impulsive and compulsive prisoners. The sample was composed of 194 male prisoners, of which 81 had been diagnosed with Antisocial Personality Disorder and 112 with Obsessive Compulsive Personality Disorder. They completed the Demographic, Crime, and Institutional Behaviour Interview; the International Personality Disorder Examination (IPDE); The Symptom Checklist (SCL-90-R) and Assessment Battery of Writing Processes (PROESC in its Spanish acronym). We found that prisoners with writing deficiencies generally have difficulties in the skills necessary to write properly due to impulsive and compulsive behaviour.